The Practical Study of Languages : A Guide for Teachers and Learners. Language and Language Learning [Series], Number 1 - Sweet, Henry ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1964)
A landmark in the literature of linguistic pedagogy is presented in this reprint of a book first published in 1899. The broad scope of this practical guide to the study of language includes extensive material on phonetic notation, general and special principles of method, grammar, vocabulary, translation, original language investigation, difficulties of language, and general considerations about language study. Other chapters discuss "dead languages", varieties of pronunciation, foreign alphabets, and the classic defense of intensive language study as a "mind-trainer". (RL)
Availability: Oxford University Press, 200 Madison Ave., New York, New York 10016 ($1.60).
Microfiche.
Keywords: Audiolingual Skills; Dictionaries; Grammar; Language Instruction; Language Research; Literary Criticism; Phonetics; Pronunciation; Second Languages; Teaching Guides; Teaching Methods; Translation; Vocabulary; Classical Languages; Learning Processes; Modern Languages; Second Language Learning; Study Guides